2019
DOI: 10.2147/jpr.s193029
|View full text |Cite
|
Sign up to set email alerts
|

<p>Anti-nociceptive and anti-inflammatory activities of crude root extract and solvent fractions of <em>Cucumis ficifolius</em> in mice model</p>

Abstract: Background: Societies in developing countries use traditional medicine as alternatives for management of pain and inflammation. The plant Cucumis ficifolius has been used in Ethiopia to treat many ailments including inflammation and pain. The objective of this study was to evaluate the antinociceptive and anti-inflammatory activities of the crude root extract and solvent fractions of C. ficifolius . Methods: The analgesic activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 41 publications
3
26
0
2
Order By: Relevance
“…Increasing PG levels within the peritoneal cavity enhances inflammatory pain by increasing capillary permeability and activating primary afferent nociceptors. 29 Echinops kebericho extract at all doses employed (100, 200 and 400 mg/kg) significantly (p < 0.01, and p < 0.001) showed peripheral analgesic activities by reducing the number of writhing with the respective values of 31.01%, 48.43%, 57.84% as compared with the negative control. These findings confirmed that the peripheral analgesic activity of the extract increased from the lower dose (100 mg/kg) to the higher dose (400 mg/kg) in dose dependent manner.…”
Section: Discussionmentioning
confidence: 91%
“…Increasing PG levels within the peritoneal cavity enhances inflammatory pain by increasing capillary permeability and activating primary afferent nociceptors. 29 Echinops kebericho extract at all doses employed (100, 200 and 400 mg/kg) significantly (p < 0.01, and p < 0.001) showed peripheral analgesic activities by reducing the number of writhing with the respective values of 31.01%, 48.43%, 57.84% as compared with the negative control. These findings confirmed that the peripheral analgesic activity of the extract increased from the lower dose (100 mg/kg) to the higher dose (400 mg/kg) in dose dependent manner.…”
Section: Discussionmentioning
confidence: 91%
“…The V. amygdalina is rich in flavonoids, steroids, necessary oil and tannins, which preferably used in animal models to predict nociception [53][54][55][56]. The certain stimulus of nociceptors can be reviewed by the initiation of inflammation that similar to acetic acid.…”
Section: Discussionmentioning
confidence: 99%
“…The peripheral analgesic activity of L. spinosa in mice was determined by formalin-induced lick test. 19 In this assay, the animals were divided into negative control, positive control or standard and test groups as mentioned in the above section. At zero-hour, test samples (HFLS, CFLS, AFLS at 500 mg/kg body weight), control and standard aspirin (50 mg/kg) were administered orally.…”
Section: Peripheral Analgesic Activitymentioning
confidence: 99%